September 11 : trauma and human bonds - Coates, Susan W.; Rosenthal, Jane L.; Schechter, Daniel S., 1962- (Relational perspectives book series, 2003)
Drawing on research from a variety of domains - clinical studies of trauma, developmental psychopathology, interpersonal psychobiology, epidemiology, and social policy - September 11: Trauma and Human Bonds addresses especially the fundamental relationship of human bonds to trauma and underscores the manner in which developments in all these fields are coming together in complementary ways that sustain a key finding: that trauma must be understood in its relational and attachment contexts. The quality of early emotional attachments, differences in attachment styles to family milieus,